CHALLENGES IN SUMMARIZING AND PARAPHRASING ACADEMIC TEXTS: PROCESSING AND PRODUCTION DIFFICULTIES IN EFL WRITERS - Yaroslav Vladimirovich Golovko (Modern American Journals, 2025)
This article examines the challenges EFL writers face when summarizing and paraphrasing academic texts, focusing on the interconnected processing and production difficulties documented across three decades of research. Summarizing and paraphrasing require deep comprehension, information selection, and linguistic reformulation, yet many EFL learners struggle with dense academic vocabulary, complex syntax, and discourse-level interpretation. Limited lexical and syntactic flexibility further restricts their ability to perform accurate transformations, often resulting in near-copy paraphrases or patchwriting. Cognitive load intensifies these problems as learners attempt to manage simultaneous reading and writing operations in a second language. The review highlights recurring developmental and pedagogical factors, including insufficient explicit instruction and anxiety surrounding plagiarism. By synthesizing empirical and theoretical findings, the article clarifies why these skills remain persistently difficult and outlines implications for more effective EAP pedagogy. Strengthening comprehension, providing explicit reformulation strategies, and supporting gradual developmental progress are essential for improving EFL writers’ academic literacy.
Keywords: EFL writing; summarizing; paraphrasing; patchwriting; academic literacy; cognitive load; reading-writing integration; linguistic reformulation